(untitled) (Scientific journal of the Fergana State University, 2023)
One of the ways of singing, which our people like to listen to and which has been preserved for centuries, is “Katta ashula”, which differs from other ways in its melody and quality. Probably for this reason, he has not lost his strength until now. This article provides information about the Katta Ashula direction and about the great Margilon singers Boltaboi Radjabov, Mamatbobo Satorov, Dzhorakhan Sultanov, Mamurjon Uzokov.